Gut microbiota profiling in injection drug users with and without HIV-1 infection in Puerto Rico - Aluthge, Nirosh; Adams, Seidu; Davila, Carmen A.; Gocchi Carrasco, Nova R.; Chiou, Kathy S.; Abadie, Roberto; Bennett, Sydney J.; Dombrowski, Kirk; Major, Angel M.; Valentín-Acevedo, Aníbal; West, John T.; Wood, Charles; et al. (Frontiers in Microbiology, 2024)
IntroductionThe full extent of interactions between human immunodeficiency virus (HIV) infection, injection drug use, and the human microbiome is unclear. In this study, we examined the microbiomes of HIV-positive and HIV-negative individuals, both drug-injecting and non-injecting, to identify bacterial community changes in response to HIV and drug use. We utilized a well-established cohort of people who inject drugs in Puerto Rico, a region with historically high levels of injection drug use and an HIV incidence rate disproportionately associated with drug use.MethodsUsing amplicon-based 16S rDNA sequencing, we identified amplicon sequence variants (ASVs) that demonstrated significant variations in the composition of microbial communities based on HIV status and drug use.Results and discussionOur findings indicate that the HIV-positive group exhibited a higher abundance of ASVs belonging to the genera Prevotella, Alloprevotella, Sutterella, Megasphaera, Fusobacterium, and Mitsuokella. However, Bifidobacteria and Lactobacillus ASVs were more abundant in injectors than in non-injectors. We examined the effect of drug use on the gut microbiome in both HIV-infected and non-infected patients, and found that multiple drug use significantly affected the microbial community composition. Analysis of differential of bacterial taxa revealed an enrichment of Bifidobacterium spp., Faecalibacterium spp., and Lactobacillus spp. in the multiple drug-injecting group. However, in the non-injecting group, Parabacteroides spp., Prevotella spp., Paraprevotella spp., Sutterella spp., and Lachnoclostridium spp. The presence of multiple drug-injecting groups was observed to be more prevalent. Our findings provide detailed insight into ASV-level changes in the microbiome in response to HIV and drug use, suggesting that the effect of HIV status and drug injection may have different effects on microbiome composition and in modulating gut bacterial populations.